Emerging antihelminthic drug resistance: Implications for mass drug administration program - Agarwal Harshita; Rajkumari Nonika (​​​One Health Bulletin, 2024)
Soil transmitted helminth infections and lymphatic diseases are significant neglected tropical diseases that pose public health challenges in both low and middle economic populations. These parasites live in the human intestine, consuming nutrients intended for the human body. Research findings suggest that the development of resistance to antihelminthic drugs is notably delayed when a combination of medications is used. Antihelminthic tablets are excellent candidates for mass drug administration (MDA) because they are highly effective and safe. Their reliability and safety make them well-suited for widespread distribution among populations at risk of parasitic worm infections. School-based deworming programs have proven successful in providing access to large numbers of children, offering them antihelminthic treatments in various settings. MDA is a key strategy in the global effort to eliminate lymphatic filariasis, with school-based deworming being an integral part of this approach. However, the longer the program lasts, the higher the risk of treatment failure is due to potential parasite resistance. Therefore, there is an urgent call for new methods to monitor and combat the emergence of drug resistance. While MDA has shown significant impact on various helminth infections, the threat of resistance remains a concern. Although there is currently no concrete evidence of resistance to common antihelminthics in humans, experiences from other infectious diseases, particularly in livestock, serve as a cautionary tale against over-reliance on these drugs for controlling lymphatic filariasis.